Peningkatan Mutu Pembelajaran Agama Hindu Dalam Mewujudkan Perubahan Mental Siswa - Dewa A. R. Wulandari; I Nengah Juliawan (UHN IGB Sugriwa Denpasar, 2018)
Advancement of science and technology is growing rapidly can lead to positive effects and negative effects on mental students, such as the still many students who are less disciplined in dressing at school or even when following the lesson in the classroom and the lower the morale owned of the students themselves. Seeing such a phenomenon is feared will be increasingly declining mental and student behavior. So in this case the improvement of the quality of Hindu religious learning is very important role for Hindus in particular and not limited to students, because religion is a guide in behaving well in accordance with religious norms that will bring good mental changes in improving attitudes and behavior behavior, personality and budhi pekerti and moral existing in learners.